A Systematic Review of Small Domain Estimation Research in Forestry During the Twenty-First Century From Outside the United States - Guldin, Richard W. (Frontiers in Forests and Global Change, 2021)
Small domain estimation (SDE) research outside of the United States has been centered in Canada and Europe--both in transnational organizations, such as the European Union, and in the national statistics offices of individual countries. Support for SDE research is driven by government policy-makers responsible for core national statistics across domains. Examples include demographic information about provision of health care or education (a social domain) or business data for a manufacturing sector (economic domain). Small area estimation (SAE) research on forest statistics has typically studied a subset of core environmental statistics for a limited geographic domain. The statistical design and sampling intensity of national forest inventories (NFIs) provide population estimates of acceptable precision at the national level and sometimes for broad sub-national regions. But forest managers responsible for smaller areas—states/provinces, districts, counties--are facing changing market conditions, such as emerging forest carbon markets, and budgetary pressures that limit local forest inventories. They need better estimates of conditions and trends for small sub-sets of a national-scale domain than can be provided at acceptable levels of precision from NFIs. SAE research is how forest biometricians at the science-policy interface build bridges to inform decisions by forest managers, landowners, and investors.